Genetic structure of Tupinambis teguixin (Squamata: Teiidae), with emphasis on Venezuelan populations. - Gols Ripoll, Ariana (2015)
Tupinambis teguixin, the common tegu, is the only species of the genus found in Venezuela. It is distributed in different bioregions in the Neotropics, some of them separated by geographic barriers that may restrict gene flow among populations. Thus, to assess this possibility, we tested the Paleogeographic hypothesis and the Riverine hypothesis for the divergence among populations. To this end, we evaluated the degree of genetic structuring in six populations of T. teguixin from Venezuela, plus one from Brazil and one from Ecuador. We used two molecular datasets, one with the populations from Venezuela (Venezuela dataset, 1 023 bp) and one including the other two (South America dataset, 665 bp), with 93 and 102 concatenated sequences from cytochrome b and ND4, and 38/37 haplotypes. We used three measures of genetic diversity: nucleotide diversity, haplotype diversity and number of polymorphic sites. Gene flow was estimated with the statistic ΦST and paired FST values. We also constructed a haplotype network. We found genetic structuring with (1) ΦST = 0.83; (2) high paired FST estimates (0.54 - 0.94); (3) haplotype networks with a well-defined geographic pattern; and (4) a single shared haplotype. The genetic structure does not seem to stem from geographic distance (r = 0.282, p = 0.209), but rather the product of an historic biogeographic event with the Mérida Andes and the Orinoco River (71.2 % of the molecular variance) as barriers. We propose the Zulia population as an Evolutionary Significant Unit and that the other populations be temporarily considered Management Units, pending further data. Populations Delta and Guri should form a single Management Unit since they share a haplotype.